Fibrinogen-Fibrin-Related Antigen Pattern in Human Blood - Jacobsen, Carl D.; Hoak, John C.; WU, Kenneth K.; Fry, Glenna L. (Thrombosis and Haemostasis, 1974)
In serum from patients with DIC at least 3 different FR-antigenic components could be found. It was difficult to demonstrate these components in the corresponding plasma samples. It is possible that a portion of these antigens formed as a result of in vitro clotting despite the presence of proteolytic inhibitors. These results suggest that the interpretation of “increased split products in serum” may be more complex than current concepts indicate.